FORGIVENESS SEBAGAI JALAN MENUMBUHKAN RASA PERCAYA PADA PASANGAN YANG PERNAH DISELINGKUHI - Widya Sari, Indah (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2023)
A person with low interpersonal trust is more likely to feel unworthy or unworthy, and it may be difficult for him or her to trust other people again. As a result, they feel ashamed or down, and have a hard time forgiving themselves or their partner. Quantitative approach is used to conduct this research. In this study, a descriptive. This study used a cross-sectional survey design. The population of this study are people who are married and have an affair. Purposive sampling method used in this study. The sample size is 138 people. The results of the correlation test with the product moment technique show that there is a correlation of 0.505 between interpersonal trust and forgiveness which is included in the strong category. There is a positive relationship between interpersonal trust and forgiveness in partners who have been cheated on. This subject has a low forgiveness score. The dimension that contributes the most to the high and low scores of forgiveness is avoidance. And being cheated on by the subject of this study has a low score of interpersonal trust. The dimension that contributes the most to the high and low scores of interpersonal trust is the propensity to trust aspect.